The Abundance of Odonata Insect in Lebak Swamp, Bukit Baru, Palembang, Indonesia - Novin Teristiandi; Riyanto Riyanto (EnviroScienteae, 2021)
Lebak swamp in Bukit Baru has been lost largely degraded and lost through reclamation activity. Lebak swamp plays important role as land resource in Bukit Baru, Palembang. The study was sonducted to study the composition of Odonata in lebak swamps in Bukit Baru, Palembang, Indonesia. The transect line (1 km) was used to collect odonata in the study area. This study recorded 8 species during the study period. 8 species were found at Site A1, 6 species at site A2, 3 species at site A3, and 6 species at site A4. The highest diversity of odonata was found in site A1, however the other sites have lower odonata diversity. The highest abundance of odonata was recorded at site A2 and A4 and dominated by Ceriagrion coromandelianum and Orthetrum sabina. Neurothemis ramburii had the lowest abund  ance at site A1 and A2, but absent at site A3 and A4. The occurrence of odonate species are lower at site around anthropogenic activity suggests the need to protect the lebak swamp so that such uncommon species will not go into local extinction. Neurothemis ramburii can become potential species to evaluate the rate of disturbed environment.